2018
DOI: 10.1371/journal.pone.0194715
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of biofilm formation on the surface of water storage containers using biosand zeolite silver-impregnated clay granular and silver impregnated porous pot filtration systems

Abstract: Development of biofilms occurring on the inner surface of storage vessels offers a suitable medium for the growth of microorganisms and consequently contributes to the deterioration of treated drinking water quality in homes. The aim of this study was to determine whether the two point-of-use technologies (biosand zeolite silver-impregnated clay granular (BSZ-SICG) filter and silver-impregnated porous pot (SIPP) filter) deployed in a rural community of South Africa could inhibit the formation of biofilm on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 20 publications
0
14
1
Order By: Relevance
“…Water quality deteriorates during household storage due to physical, chemical, and microbiological processes [ 2 , 3 , 4 , 5 , 6 ]. If the storage containers are not properly or regularly cleaned and hygiene behaviours are poor inside the household, a biofilm forms inside the container [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Water quality deteriorates during household storage due to physical, chemical, and microbiological processes [ 2 , 3 , 4 , 5 , 6 ]. If the storage containers are not properly or regularly cleaned and hygiene behaviours are poor inside the household, a biofilm forms inside the container [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The quality of water stored in households might provide the indicators of the level of secondary contamination by comparing the levels with that of the source water. Such a comparison would also be very important to model household transmission dynamics to understand pathogen flow pathways and to provide proper interventions [1214]. In Cox’s Bazar, since the Rohingya population is living in a small and highly crowded area and since a huge number of people are using a single water point (on an average, 192 people are getting water from a single tubewell), it is difficult to testify water quality from every household.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, fecal indicator bacteria presence was not associated with container type or opening, but was associated with storage time; no difference was found in water or biofilm gene copies after local cleaning (n = 2). Lastly, Budeli et al confirmed biofilm formation via scanning electron microscopy, in plastic storage container surfaces within 24 h of exposure to untreated water 33 . After filtration with silver nanoparticle containing ceramic filters, biofilm formation was visually apparent at 14-21 days or 3-14 days, depending on filter.…”
Section: Introductionmentioning
confidence: 94%